Mengajarkan Toleransi melalui Permainan Tradisional - Soliha, Imro Atus; Fadilah, Yulina (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research examines the role of traditional games in teaching tolerance through a combination of local values and Islamic teachings. The objective of the study is to analyze how games like Engklek, Congklak, and Sepak Takraw can develop students' cooperation and respect for others, in line with Islamic concepts of brotherhood (ukhuwah) and cooperation (ta'awun). Using a qualitative research method, including observations and interviews with educators, the study reveals that traditional games help to foster social interaction while also imparting moral values, enhancing students' understanding of tolerance. The discussion emphasizes the importance of integrating traditional media into Islamic education, merging local wisdom with Islamic principles to build a culture of tolerance and collaboration. The study concludes that traditional games serve as an effective tool for character education in Islamic contexts.